It's snowing! It's snowing! : winter poems - Prelutsky, Jack.; Abolafia, Yossi (New York : HarperCollins, 2006)
Presents a collection of over a dozen, illustrated, rhyming poems about winter.
"3 Reading alone"--Cover.
Booklist
Kirkus Review
School Library Journal
4.4
K-3.
Keywords: Children's poetry, American; Snow -- Juvenile poetry; Winter -- Juvenile poetry; American poetry; Snow -- Poetry; Winter -- Poetry; American poetry; Snow -- Poetry; Winter -- Poetry; Readers (Elementary).